Nonconventional Principle of Conversion of Heat into Cold in an Internal Combustion Engine - Hlavna, Vladimir; Sojcak, Dusan; Istenik, Rastislav (Communications - Scientific letters of the University of Zilina, 2006)
The paper presents results achieved by a team of 12 researchers from the Faculty of Mechanical Engineering of the University of Žilina who participated in the solution of the project of the above-mentioned title within the period of the years 2002 – 2005. The basic research project focuses on the cooling internal combustion engine as an element of qualitatively new equipment designed for more effective utilization of fuel energy by a nonconventional progressive principle of heat conversion cooled by thermocompression. The issue of permanently sustainable life is approached from three hierarchical levels: a first level is a cooling internal combustion engine; a second level is a combined cogeneration complex power source; and a third level is a permanently sustainable power system. The cooling internal combustion engine is actually the basic element of the subsystem in the three-level complex of permanently sustainable life. It is still necessary to verify expected advantages of this unconventional combustion engine, potential savings of primary energy and foresee possible problems arisen during the simulation of the engine.